Preoperative management in octogenarian patients with rectal cancer - Arthur M. Damasceno; Rubens Kesley; Marcus Valadão; Fabrício Braga; Cristiane A. D'Almeida; Marcos B. Pitombo (Heliyon)
Background: In recent years, the rise in average lifespan has been linked to an increase in the occurrence of diseases associated with aging worldwide. Rectal tumors often occur in elderly patients. Methods: Between January and August 2024, 6 experts in colorectal cancer met to develop an algorithm to organize the interdisciplinary and multimodal preoperative approaches in the octogenarian population with rectal cancer. To develop the algorithm, we conducted a straightforward search within the PubMed database and also reviewed the citations of the most pertinent articles we discovered. The quality of the methods used in the final selection of 76 sources was evaluated, every single source was scrutinized and analyzed, and a team of six experts created an algorithm. Results: An algorithm for preoperative management of octogenarian patients with rectal cancer was created to encapsulate essential information and provide a contemporary resource for physicians, surgeons, physiotherapists, and nutritionists to utilize in optimal clinical practice. Conclusions: Octogenarian patients with rectal cancer are special-character groups and require specific preoperative management to better the surgical outcome.